2002
DOI: 10.1128/jcm.40.2.620-626.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiles of Group B Streptococcal Surface Protein Antigen Genes: Relationship to Molecular Serotypes

Abstract: The study of surface protein antigens of group B streptococci (GBS) is important for understanding of the pathogenesis and epidemiology of infection, and several of these antigens have been proposed as components of GBS conjugate vaccines. In a previous study, we developed a novel PCR-and-sequencing system for identification of GBS serotypes and serosubtypes based on the capsular polysaccharide synthesis (cps) gene cluster. In this study, we used published sequences to develop PCR assays for identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
110
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(132 citation statements)
references
References 30 publications
22
110
0
Order By: Relevance
“…Molecular serotyping methods would probably increase their typeability. However, a decreased capacity for capsular polysaccharide synthesis, noncapsulated phase variation, or cps gene cluster modification could prevent proper serotype identification (8,27). Our study confirms the high level of beta-lactam susceptibility of GBS (6,40).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Molecular serotyping methods would probably increase their typeability. However, a decreased capacity for capsular polysaccharide synthesis, noncapsulated phase variation, or cps gene cluster modification could prevent proper serotype identification (8,27). Our study confirms the high level of beta-lactam susceptibility of GBS (6,40).…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies reported occurrence rates of NT strains ranging from 1 to 18% (3,21,27,50). Our numbers (7.1%) included colonizing, noninvasive, and invasive isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships between serotypes and surface protein genes were noted but to a lesser degree than previously reported (10,12). The association of serotypes Ia, Ib, and II with the alpha protein, of serotype III with Rib, and of serotypes V and VIII with Alp3 was found, but these associations were not absolute.…”
mentioning
confidence: 56%
“…In two cases (reference strain Prague 10/84 and a bovine strain), no surface protein gene was detected. The absence of a surface protein gene in GBS isolates, although rare, has previously been reported (10).…”
mentioning
confidence: 97%
“…4,49,52,53 The antibody response was observed to persist for over a year in the mother and the passive protection in the neonate persisted for at least three months, hence it would be expected to protect against late-onset disease. 4,48,50,54 Moreover, the IgG antibody is bactericidal. 4 At present, a fully effective vaccine should be pentavalent, so as to induce antibodies against all five GBS serotypes that cause disease (see section on Microbiological procedures in detecting GBS colonization), but a univalent GBS vaccine active against a single surface protein shared by the five serotypes is under development.…”
Section: The Gbs Vaccinementioning
confidence: 99%